Chemical composition and antifungal activity of essential oils extracted from Pimenta dioica and Piper auritum leaves grown in Mexico - Anayancy Lam-Gutiérrez; Teresa Ayora-Talavera; Eduardo Raymundo Garrido-Ramírez; Víctor Manuel Ruíz-Valdiviezo; Jorge Martín Guzmán-Albores; Jairo Cristóbal-Alejo (Cogent Food & Agriculture)
Diseases caused by mycotoxin-producing fungi, especially Aspergillus ochraceus and Fusarium moniliforme, are on the rise, leading to contamination of agricultural products and seeds during processing and storage, resulting in significant economic losses and posing serious health risks to humans and animals. Controlling these diseases primarily relies on synthetic fungicides, which can leave behind toxic residues harmful to human and animal health, as well as the environment. Various strategies have been proposed for controlling these fungal diseases, including biological control using essential oils (EOs) derived from plants. EOs extracted from plants of the Piper and Pimenta genera contain secondary metabolites with antimicrobial properties. This study aims to analyze the effect of EOs from Piper auritum and Pimenta dioica on the fungi A. ochraceus and F. moniliforme. The EOs were obtained through steam distillation, and their antifungal activity was assessed using minimum inhibitory concentration (MIC), minimum fungicidal concentration (MFC), and % sporulation. The phytochemical composition of the EOs was determined by GC-MS. The fungal species exhibited susceptibility to the EOs, with MIC and MFC values of 0.16 and 1.21 mg/mL, respectively, for P. dioica against A. ochraceus, and 0.43 mg/mL against F. moniliforme. Meanwhile, the MIC and MFC values for P. auritum were 0.16 and 15 mg/mL, respectively, against A. ochraceus. The EOs demonstrated effective antifungal activity, likely attributed to the presence of bioactive compounds.